Corpos que dançam: processos criativos a partir dos princípios do Karatê-do - SILVA, Evelin Beatriz Cardoso da (2018)
This paper aims to apply the principles of karate-do in the creative process in dance. Seeks to reflect the choreographic process through the fundamentals of Taikyoku Shodan kata. As a theoretical framework about the process of creation Fayga bring Ostrower (1987), about the teachings of karate-Gichin Funakoshi (2000) and more specifically in dance Lindemberg dos Santos (2011) and Ana Flávia Mendes (2010). This is a search action to require the active involvement of the researcher and the action on the part of people committed to the choreographic process in dance school Ribalta. From a descriptive approach to motion analysis was done according to the studies of Rudolf Laban (2002), Ciane Fernandes (2002) and Lenira Rengel (2006). Therefore, the result reveals another way for the creation in contemporary dance.